An Experimental and Numerical Study of Diorite-Porphyrites With Different Weathered Degree in the Direct Shear Test - Fan, Haotian; Sun, Shaorui; Le, Huilin; Zhu, Feng; Wang, Wuchao; Liu, Yong; Wang, Jin (Frontiers in Earth Science, 2020)
There are many well-developed weathered diorite-porphyrites, except main rocks, in the Jurong pumped storage power station of Jiangsu Province, China. Due to different geological environments, diorite-porphyrites emerged by invading faults and can alter from weakly weathered to strongly weathered in less than half a year, which directly affected the safety and stability of hydraulic structures. Therefore, it is important to study the mechanical properties of diorite-porphyrites with different degrees of weathering. The main purpose of this paper is to investigate the effects of the different degrees of weathering on the shear behavior and the mechanical properties of diorite-porphyrites. Experimental and numerical direct shear tests were performed under normal stresses of 0.54, 0.77, 1.53, and 2.30 MPa on strongly weathered, moderately weathered, and weakly weathered samples, respectively. The test results show that with the increase of the degree of weathering, the chemical composition changed; the cohesion and the internal friction angle both decreased. Crack initiation, propagation, and coalescence were all observed with the numerical simulations using two-dimensional particle flow code (PFC2D). The numerical results are in good agreement with the experimental results, and this numerical approach can reproduce the shear behavior of the weathered diorite-porphyrites under different shear conditions. Based on the gradient of the pre-peak stage, the peak stress, and the residual stress, the shear stress–displacement curves can be categorized into three types: type A (mostly for the strongly weathered diorite-porphyrite), type B (mostly for the moderately weathered diorite-porphyrite), and type C (mostly for the weakly weathered diorite-porphyrite). A set of microparameters that can properly simulate the weathered diorite-porphyrites in PFC2D was proposed, which can be applied in the engineering simulation for further analysis.